Eloquence (‘Beredsamkeit’) and Rhetoric (‘Rhetoric’) as Terms and Lexemes. The Concept of Rhetoric in the Dictionary Deutsches Wörterbuch of Jacob und Wilhelm Grimm in the Context of European Idea of the ‘National Language’ in the 19th Century (ENTHYMEMA, 2013)
This article focuses on the European heritage of rhetoric in the 18th century within the dictionary Deutsches Wörterbuch by the brothers Jacob und Wilhelm Grimm as a case of transformation of knowledge from the classical language of scholarship - Latin - to the vernacular of Germany in scholarly literature. The dictionary Deutsches Wörterbuch begun by the Grimm brothers was finally edited in the 20th century. It is a source for the historical terms used in the German language in the written and published books prior to the first half of the 19th century. The Deutsches Wörterbuch presents historical terms, which are documents of the usage of the German language since the time of Luther, and also newly created terms resulting from translations. The concept of «rhetoric» in the dictionary demonstrates this dichotomy. The effects this dictionary had on its readers’ understanding of language will be shown in contrast to other European movements of national identity in the 19th century.